Effect of Some Agronomic Practices to Increase Maize Yield in Ghana (Journal of Science and Technology, 2016)
Low plant densities of maize are often observed in fields of farmers practising no-till agriculture which causes low grain yield in Ghana. With the increasing population and consumption of maize in the country, research must be directed to solve this problem to enhance maize production. In this paper, a 2x3 factorial experiment in randomized complete block design with 4 replications was carried out at Wioso in the Atwima-Nwabiagya District in the Ashanti Region of Ghana during the major season of 2007 in order to come out with the best practices in maize production. The objectives of the study were to determine the right period of refilling maize field and the comparative effect of refilling with seed and seedling on the growth, optimum population density, and yield of maize. The factors were material for refill, which was either seeds or seedlings, and time of refilling either at 5, 10, and 15 days after planting. The results showed that refilling with seedlings produced the greatest positive effect in the number of leaves per plant, leaf length, leaf diameter, plant height and stem girth. Furthermore, refilling with seedlings contributed more to the optimum plant population density. Total grain yield when seedlings were used as refill was 967kg per hectare more than when seeds were used as refill material. On the other hand, plants from seeds refill were weak, lodged more and allowed much solar radiation penetration to the ground. Grain yield from seed refill plants was 6%, whilst seedling refill plants contributed 34% to the total grain yield. Refilling at 5 days after planting induced greater growth than 10 or 15 days after planting. The results indicate that it is possible to do refilling in maize field by using seedling as this contributes more than the traditional method of using seeds.